Ultramafic Rocks and Their Alteration Products From Northwestern Allaqi Province, Southeastern Desert, Egypt: Petrology, Mineralogy, and Geochemistry - Abdel-Rahman, A. M.; El-Desoky, H. M.; Shalaby, B. N. A.; Awad, H. A.; Ene, Antoaneta; Heikal, M. A.; El-Awny, H.; Fahmy, W.; Taalab, S. A.; Zakaly, Hesham M. H. (Frontiers in Earth Science, 2022)
The ophiolitic rocks, island arc metasediments, and granitic rocks are encountered in the study of the Allaqi province. The present study concentrated on ultramafic rocks and their various forms of hydrothermal alteration. Ophiolites commonly occur as dismembered rock sequences and have different types of hydrothermal alteration products. Ophiolites contain the essential type as serpentinites and talc-carbonate rocks, listwaenites, and amphibolites along shear zones and faults. Listwaenite is one of the most significant rocks in this area because it contains gold. The whole serpentinite rocks are affected by regional metamorphosis into greenschist facies. Geochemically, Neoproterozoic serpentinites fall into SSZ ophiolites, alpine-type peridotite, formed in the forearc peridotite tectonic environment. Regardless, the listwaenite and talc-carbonate rocks revealed that they trend to silica, carbonate, and talc. Listwaenites are classified into two types: carbonate-rich listwaenites and silica–carbonate-rich listwaenites. Magnetite, chromite, galena, and gold are the most typical ores recorded in this research.